Practice of comorbidity management based on community chronic disease health management support centers: an introduction and discussion - Mengyun SUI; Sheng ZHANG; Yuheng WANG; Qinghua YAN; Fei WU; Chen FU; Minna CHENG; Yan SHI (Zhongguo gonggong weisheng)
This study aims to elucidate the practical approaches and experiences of comorbidity management in Shanghai city, providing a reference for the Yangtze River Delta and other regions in China. Shanghai city has developed a comprehensive and closed-loop chronic disease health management system, which includes pre-diagnosis risk assessment and identification with tagged classification, intra-diagnosis standardized monitoring, data sharing integration, multidisciplinary collaboration, decision support, and post-diagnosis complication screening, intelligent follow-up, patient self-management, standardized health education, and re-evaluation. This system provides continuous medical care for patients with chronic comorbidities. Future potential directions and pathways for chronic comorbidity management include optimizing the social collaborative governance mechanism, further improving the network of community and social resource provision, refining the standards and mechanisms for referral of chronic disease patients, formulating shared decision-making and dynamic, continuous, and personalized care plans, and establishing a multidisciplinary collaboration mechanism for comorbidity patients in primary healthcare institutions.